Cooperative multi-agent reinforcement learning in sparse-reward, partially observable 3d environments with curriculum-transfer learning - Denkema, De Wet (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.